EFFECT OF CAPITAL STRUCTURE, COMPANY GROWTH AND PROFITABILITY OF CORPORATE VALUES IN COAL MINING SUBSECTOR COMPANIES - Natalia, Natalia (Asosiasi Dosen Akuntansi Indonesia, 2019)
The objective of this research is to find out and analyse the influence of capital structure, company growth, and profitability partially and simultaneously on the value of the company in coal mining companies listed on the Indonesia Stock Exchange (IDX). The population of this research is 21 coal mining companies listed on the Indonesia Stock Exchange (IDX) with 2013 to 2017. Observation years were selected using the purposive sampling method. Data is processed using panel data regression statistical test methods. The results of this study prove that the capital structure and profitability partially influence the value of the company in coal mining companies listed on the Indonesia Stock Exchange. While the growth of the company does not affect the value of the company in coal mining companies listed on the Indonesia Stock Exchange. The simultaneous capital structure, company growth and profitability simultaneously influence the value of the company in coal mining companies listed on the Indonesia Stock Exchange.